Discovery of extremophilic cellobiohydrolases from marine Aspergillus niger with computational analysis. (April 2022) - Cai, Li-Nian; Lu, Tao; Lin, Dong-Qiang; Yao, Shan-Jing
Abstract: To discover extremophilic cellobiohydrolases from marine Aspergillus niger, two cellobiohydrolase genes ( cel7a and cel7b ) were cloned from marine A. niger genome and their speculated mature peptides were performed with amino acid composition analysis and molecular dynamics simulation. The results revealed that An Cel7B was more thermostable than An Cel7A. Subsequently, two cellobiohydrolases were obtained by directed expression in marine A. niger and purified to homogeneity with anion exchange chromatography. Enzymatic property study revealed that An Cel7B was thermostable and its half-lives at 80, 90 and 100 °C were 90, 35 and 15 min, respectively, which was comparable with those from thermophiles. It was proposed that more charged amino acid residues in An Cel7B engendered more salt bridges, and then made the overall structure more thermostable, which was further proved by site-specific mutagenesis study. In addition, it was found that An Cel7A exhibited acidophilic property (optimal pH was 2.5–4.5) and An Cel7B exhibited halotolerant property (optimal salt concentration was 0.9 M NaCl). In this study, two cellobiohydrolases possess the potential for industrial application under acidic, high salt concentration and high temperature conditions, and the thermostable mechanism is beneficial for the directed evolution of enzymes. Graphical Abstract: ga1 Highlights: The thermostable cellobiohydrolase An Cel7B was discovered by computational analysis. Discovery of thermostable An Cel7B from mesophile A. niger . More charged residues and salt bridges made An Cel7B more thermostable. The cellobiohydrolase An Cel7A was acidophilic and An Cel7B was halotolerant.